Pengaruh Penanaman Modal Asing, Penanaman Modal dalam Negeri, dan Belanja Modal terhadap Industri Pengolahan dan Produk Domestik Regional Bruto di Provinsi Sulawesi Selatan - Nurilmih Nurilmih; Junaiddin Zakaria; Dahlia Baharuddin (Departement of Mathematics Education, 2023)
This research was conducted with the aim of understanding 1) the effect of foreign investment on the processing industry in South Sulawesi Province; 2) the effect of domestic investment on the processing industry in South Sulawesi Province; 3) the effect of capital expenditure on the processing industry in South Sulawesi Province; 4) the effect of foreign investment on the gross domestic product in South Sulawesi Province; 5) the effect of domestic investment on the gross regional domestic product in South Sulawesi Province; 6) the effect of capital expenditure on the gross regional domestic product in South Sulawesi Province. This study uses secondary time series data from 2006 to 2021. The data is analyzed using the Eviews 10 application using the Error Correction Model to analyze short-term and long-term effects. The results of the study show that in the long run: 1) FDI has a positive and significant effect on the processing industry in South Sulawesi Province; 2) Domestic Investment has a positive and significant effect on the processing industry in South Sulawesi Province; 3) positive and significant capital expenditure for the processing industry in South Sulawesi Province; 4) FDI is positive and not significant to GRDP in South Sulawesi Province; 5) Domestic Investment has a positive and significant effect on GRDP in South Sulawesi Province; 6) capital expenditure has a positive and significant effect on GRDP in South Sulawesi Province. That means that the role of the government, private sector, and society is needed to increase income goods from side production and economic spending. Expected that through strengthening investment and macroeconomic stability as well as determining economic activities that can increase the influence of the processing industry and increase GRDP